2011
DOI: 10.1093/pch/16.1.e1
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telephone reminders and home visits to improve measles, mumps and rubella immunization coverage rates in children

Abstract: Telephone reminder systems have some benefit in increasing child immunization coverage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
(23 reference statements)
1
18
0
1
Order By: Relevance
“…All nine interventions that included a home visit component showed some evidence of effectiveness 5154 55 57 64 72 74 75 81 Although two of three studies considering outreach interventions alone were not effective, they were either small or had significant loss to follow-up 6768 The three studies using escalating intervention intensity seemed particularly effective, which is consistent with the previous review 55…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…All nine interventions that included a home visit component showed some evidence of effectiveness 5154 55 57 64 72 74 75 81 Although two of three studies considering outreach interventions alone were not effective, they were either small or had significant loss to follow-up 6768 The three studies using escalating intervention intensity seemed particularly effective, which is consistent with the previous review 55…”
Section: Discussionsupporting
confidence: 77%
“…The hypothesis offered was that younger children would be attending services more regularly and thus have higher uptake, whereas older children might not and thus be more responsive to reminders. Of two Canadian studies examining MMR coverage in deprived areas, one controlled before-and-after study found that telephone reminders increased MMR uptake in children not UTD at 24 months;74 however, the other non-controlled time series found increases in intervention (targeted phone, mail and outreach) and non-intervention sites, with no decrease in socioeconomic disparities 75…”
Section: Resultsmentioning
confidence: 99%
“…12 1524,30,31 Canada 3 2527 ; U.K. 1 28 ; Multiple non-U.S. locations 1 29 Vaccination programs in WIC settings 3 32–34 2 32,34 Childhood Series 3 32–34 U.S. 3 32–34 Increasing community demand for vaccinations Client reminder & recall systems 24 46,13,3554 11 13,36–38,40,45–48,52,53 Influenza 8 13,3541 Pneumococcal 1 42 Influenza and pneumococcal 1 43 DTP/DTaP 1 44 MMR 2 5,45 Tetanus 2 46,47 Other childhood series 9 4,6,48–54 U.S. 18 4,6,35,36,38,4046,48–52,54 Denmark 1 13 New Zealand 1 53 U.K. 1 39 Canada 3 5,37,47 Client or family incentive rewards 7 c,5562 No economic review conductedb Hepatitis B 4 5962 Influenza 1 57,58 Childhood series 2 55,56 …”
Section: Chartmentioning
confidence: 99%
“…3 32–34 Increasing community demand for vaccinations Client reminder & recall systems 24 46,13,3554 11 13,36–38,40,45–48,52,53 Influenza 8 13,3541 Pneumococcal 1 42 Influenza and pneumococcal 1 43 DTP/DTaP 1 44 MMR 2 5,45 Tetanus 2 46,47 Other childhood series 9 4,6,48–54 U.S. 18 4,6,35,36,38,4046,48–52,54 Denmark 1 13 New Zealand 1 53 U.K. 1 39 Canada 3 5,37,47 Client or family incentive rewards 7 c,5562 No economic review conductedb Hepatitis B 4 5962 Influenza 1 57,58 Childhood series 2 55,56 U.S. 4 5962 Australia 2 55,56 Germany 1 57,58 Vaccination requirements for child care, school & college attendance 2 63,64 No studies found Hepatitis B 1 63 Varicella 1 64 U.S.…”
Section: Chartmentioning
confidence: 99%
“…14,15 Three observational studies from the UK and Canada comparing outcomes in control areas with those implementing combinations of postal or phone reminders with home visiting found improved immunisation uptake. [16][17][18] Wales has well developed services to deliver the childhood immunisation program, utilizing birth registers and a universal call/recall system which identifies and allows follow up of unimmunised children. The system achieves a high uptake for those who respond to invitations and attend their local general medical practice premises.…”
mentioning
confidence: 99%